ANALYSIS OF THE PERFORMANCE AND FINANCIAL PERFORMANCE OF THE CREDIT COOPERATIVE (Case Study of Koperasi Swastisari in Kupang) - Hakim, Fadlurahman (Khairun Law Journal, 2021)
The objective of this research is to know the level of financial health of Koperasi Swastisari Credit 2012-2016 based on the Regulation of State Minister of Cooperatives and Small and Medium Enterprises of Republic of Indonesia No.06 / PER / DEP.6 / IV / 2016 concerning capital aspect, earning asset quality, management, liquidity, efficiency, independence and growth as well as cooperative identity.This research is a type of descriptive evaluative research. The subject of this research is Credit Cooperative (Kopdit) Swastisari in which the object of evaluation is financial health Kopdit Swastisari. Data analysis techniques in this study using descriptive analysis. In this research data is collected through documentation and interview method. The results showed that the healthlevel of the 2012-2016 Swaddle Kopdit was in fairly healthy category with the average score of 78.06 with details: (1) the capital aspect was averaged 12.24 and was in the healthy category; (2) aspect of productive asset quality in the mean score 17,25 and in healthy enough category; (3) management aspect was score 13,07 and was in healthy category; (4) the efficiency aspect was averaged 15.00 and was in the healthy category; (5) liquidity aspect in the average score of 7.25 and is in the less healthy category; (6) aspect of independence and growth average score 6.25 and in the category of healthy enough; (7) the aspect of cooperative identity is averaged score of 7.00 and is in fairly healthy category. (8) the level of health of the Swedy Kopdit for 5 years(2012-2016) in a row obtained the total score of 70.35; 71.05; 72.45; 72.70; 72.50 and 78.06 are in fairly healthy categories.Using Trend Analysis least square method taken from the total health ratio of Swasti Sari Kopdit Period (2012-2016) obtained estimates of the results of the health ratio assessment in the coming year (2017-2020), the score obtained is 73.58; 74.17; 74.76 and 75.35 which indicate a good prospect for the next 5 year.